2008
DOI: 10.1029/2008gl035764
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of black carbon by ice crystals over the northern Pacific

Abstract: [1] Airborne measurements over the northern Pacific are evaluated to characterize properties of black carbon (BC) in cirrus crystal residuals and background aerosols in the upper troposphere. Although the mass and number concentrations of BC were 7 -25 times lower in crystal residuals than in particles outside of cloud, twice as many of the residuals (31%) contained BC compared to 17% of the particles in cloud-free air. In addition the average mass equivalent diameter (MED) of BC was 10% larger in crystal resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 19 publications
(23 reference statements)
5
34
0
Order By: Relevance
“…Our results differ in that collisions are shown to dominate over nucleation or freezing for transfer of aerosol into the ice crystals. This is in agreement with recent work by Baumgardner et al (2008), who suggested that impaction scavenging might dominate over nucleation scavenging for black carbon scavenging into ice crystals. Our study also implemented the below-cloud scavenging parameterization of Croft et al (2009), which accounts for the higher aerosol removal by below-cloud scavenging in comparison to the results in Fig.…”
Section: In-cloud Scavenging Sensitivity Simulationssupporting
confidence: 82%
See 1 more Smart Citation
“…Our results differ in that collisions are shown to dominate over nucleation or freezing for transfer of aerosol into the ice crystals. This is in agreement with recent work by Baumgardner et al (2008), who suggested that impaction scavenging might dominate over nucleation scavenging for black carbon scavenging into ice crystals. Our study also implemented the below-cloud scavenging parameterization of Croft et al (2009), which accounts for the higher aerosol removal by below-cloud scavenging in comparison to the results in Fig.…”
Section: In-cloud Scavenging Sensitivity Simulationssupporting
confidence: 82%
“…Jacobson (2003) found for a one-dimensional study that aerosol mass was primarily scavenged by nucleation, whereas aerosol number was primarily scavenged by impaction processes. Recently, Baumgardner et al (2008) have suggested that for black carbon, scavenging by ice crystals is dominated by impaction as opposed to nucleation processes.…”
mentioning
confidence: 99%
“…The findings from this study agree with those of and show that during periods of precipitation, BC exhibited a slightly lower degree of mixing (36 ± 14% thickly coated), possibly implying an enhanced scavenging due to the mixing with volatile/semi-volatile materials. However, rather than nucleation scavenging, the inertial scavenging of BC could play a more significant role when incorporated into ice particles of cirrus (Baumgardner et al, 2008), and the impaction with hydrometeor may also be an important contributor to BC removal by precipitation (Jacobson, 2004). More work is necessary to investigate the role of particle inertia and different mechanisms for BC to be nucleation activated as IN.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cold clouds (T < 258 K), we assume that only dust and hydrophobic BC can serve as IN and hence be removed by scavenging (Chen et al, 1998;Andreae and Rosenfeld, 2008). Cozic et al (2007) find that the BC fraction scavenged into cloud droplets decreases with decreasing temperature, from 60 % at 0 • C to 10 % at < −20 • C. However, it must be recognized that the scavenging of BC by cold clouds is highly uncertain (Karcher et al, 2007;Baumgardner et al, 2008;Cozic et al, 2008;Targino et al, 2009;Stith et al, 2011).…”
Section: Wet Depositionmentioning
confidence: 99%